2022
DOI: 10.1371/journal.pcbi.1010390
|View full text |Cite
|
Sign up to set email alerts
|

A computational framework for modelling infectious disease policy based on age and household structure with applications to the COVID-19 pandemic

Abstract: The widespread, and in many countries unprecedented, use of non-pharmaceutical interventions (NPIs) during the COVID-19 pandemic has highlighted the need for mathematical models which can estimate the impact of these measures while accounting for the highly heterogeneous risk profile of COVID-19. Models accounting either for age structure or the household structure necessary to explicitly model many NPIs are commonly used in infectious disease modelling, but models incorporating both levels of structure presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Our findings have since been corroborated by subsequent additions to the literature on the topic of quantifying the effect of household bubbles on the transmission of SARS-CoV-2, with a variety of modelling approaches represented [28, 29]. In detail, Danon et al .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our findings have since been corroborated by subsequent additions to the literature on the topic of quantifying the effect of household bubbles on the transmission of SARS-CoV-2, with a variety of modelling approaches represented [28, 29]. In detail, Danon et al .…”
Section: Discussionsupporting
confidence: 66%
“…They found that whilst the creation of support bubbles between a single-person household and another household of any size had a small impact on transmission, scenarios where all households form a bubble would be highly likely to cause extensive transmission. Later work from Hilton et al [29] provided an infectious disease modelling framework formulated in terms of tractable systems of ordinary differential equations that includes explicit representation of age/risk structure and household structure. Our results are in agreement with their findings on the usage of short-term social bubbles, which suggested that shortterm relaxation in mixing restrictions would have a small but non-negligible impact on the epidemic dynamics, with larger temporary bubbles and longer mixing periods associated with higher prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed that the household structure has a profound impact on the transmission of infectious diseases [12][13][14]. Although previous research has attempted to associate both household-and individual-level attributes in a unified manner, they most simply fit the marginal distribution of household-level attributes (e.g., household size), and thus fail to capture and reproduce the interdependencies among agents within the same household [15].…”
Section: Introductionmentioning
confidence: 99%
“…Household studies are considered the gold standard for the study of infectious disease transmission, as they provide a setting in which transmission events can be pinned down to one or a small number of potential infectors [7][8][9][10][11][12][13][14][15][16][17][18]. Classical analyses of household data use statistical regression techniques to estimate the fraction of persons that are infected over the course of a household outbreak (the secondary attack rate or SAR), stratified by person-type and household characteristics [19].…”
Section: Introductionmentioning
confidence: 99%